2020
DOI: 10.1021/acs.est.0c03207
|View full text |Cite
|
Sign up to set email alerts
|

2D N-Doped Porous Carbon Derived from Polydopamine-Coated Graphitic Carbon Nitride for Efficient Nonradical Activation of Peroxymonosulfate

Abstract: Nitrogen-doped carbon materials attract broad interest as catalysts for peroxymonosulfate (PMS) activation toward an efficient, nonradical advanced oxidation process. However, synthesis of N-rich carbocatalysts is challenging because of the thermal instability of desirable nitrogenous species (pyrrolic, pyridinic, and graphitic N). Furthermore, the relative importance of different nitrogenous configurations (and associated activation mechanisms) are unclear. Herein, we report a “coating-pyrolysis” method to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(113 citation statements)
references
References 60 publications
3
110
0
Order By: Relevance
“…The current at both activatorcovered electrodes showed conspicuous drops after injecting the IO 4 − species, which were attributed to interactions between the activators and IO 4 − (i.e., electron-transfer processes), indicating the formation of activator−periodate* complexes. 38 Both activator-modified GCEs subsequently exhibited significant current jumps after 4-CP was added. The observed current increases were attributed to the electron-transportation processes from the electron donor (i.e., the injected 4-CP) to the acceptor (i.e., activator−periodate* complexes).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The current at both activatorcovered electrodes showed conspicuous drops after injecting the IO 4 − species, which were attributed to interactions between the activators and IO 4 − (i.e., electron-transfer processes), indicating the formation of activator−periodate* complexes. 38 Both activator-modified GCEs subsequently exhibited significant current jumps after 4-CP was added. The observed current increases were attributed to the electron-transportation processes from the electron donor (i.e., the injected 4-CP) to the acceptor (i.e., activator−periodate* complexes).…”
mentioning
confidence: 98%
“…Nevertheless, the role of N should not be ignored since N-doping promoted the water dispersity of rGO (Supporting Information, Figure S7) and the subsequent adsorption of electrophilic contaminants (e.g., 4-CP). 38 The effect of the solution's initial pH (pH 0 ) on the efficiency of 4-CP removal in the N-rGO-CoSA/IO 4 − system was investigated by setting the pH 0 parameter at 3.2, 5.1, 7.0, and 8.9. Higher pH conditions were not studied to avoid the alkali-mediated activation of IO 4 − .…”
mentioning
confidence: 99%
“…The case here is contrary to the known mediated electron transfer process in carbon and noble metal catalyzed reactions wherein the addition of the pollutant accelerates PMS decomposition. 10,58,[60][61][62] The sharp contrast herein indicates that the spatial-connement of Co nanocrystals may alters the electron transfer process from pollutants to PMS.…”
Section: Mechanistic Insightsmentioning
confidence: 93%
“…1 O 2 -Dominated oxidation processes were frequently reported, and metal oxides and carbon materials including porous carbon, graphenes, and carbon nanotubes were the catalysts. 74,154,155 As mentioned above, the degradation processes are largely dependent on the properties of ROS. Zhu and co-authors reported the 1 O 2 -dominated degradation process in the PDS/β-MnO 2 catalytic system that showed excellent degradation performance at pH of 5.…”
Section: Effects Of Anions On Persulfate-based Aops For Sow Treatmentmentioning
confidence: 99%